2021
DOI: 10.15420/ecr.2021.04
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Prognostication of Patients with Coronary Stenoses in the Pre- and Post-PCI setting: Comments on TARGET FFR and DEFINE-FLOW Trials Presented at TCT Connect 2020

Abstract: The body of evidence for the use of coronary physiology assessments to guide percutaneous coronary intervention (PCI) has been growing continuously in recent decades. Two studies presented during TCT Connect 2020 added insights into the prognostic value of coronary physiology measurements in pre- and post-PCI settings. The first study, TARGET FFR, assessed whether a post-PCI fractional flow reserve (FFR)-guided incremental optimisation strategy (PIOS) was superior to angiography-guided PCI. The second study, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…The DEFINE-FLOW trial [ 52 ] randomized 430 patients with a positive FFR to undergo or postpone PCI according to CFR values (< or ≥2.0). The trial reported an increase in myocardial revascularization and infarction when deferring PCI in hemodynamically significant lesions with preserved CFR.…”
Section: From Stenosis To Ischemia: New Concepts Of Coronary Physiologymentioning
confidence: 99%
“…The DEFINE-FLOW trial [ 52 ] randomized 430 patients with a positive FFR to undergo or postpone PCI according to CFR values (< or ≥2.0). The trial reported an increase in myocardial revascularization and infarction when deferring PCI in hemodynamically significant lesions with preserved CFR.…”
Section: From Stenosis To Ischemia: New Concepts Of Coronary Physiologymentioning
confidence: 99%